Sustainable Facilities Management (SFM) Initiatives in Malaysia Hotel Industry - Abu Talib, Alyaa Afifah; Muhamad Ariff, Nor Rima; Hasim, Mohamad Sufian; Hanafiah, Mohd Hafiz; Sivam, Alpana (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study offers valuable insights into the implementation of Sustainable Facilities Management (SFM) initiatives within Malaysia's hotel industry. By drawing upon traditional organizational theory, the research identifies sustainable measures at strategic, tactical, and operational levels. Environmental issues have gained increasing recognition among hoteliers worldwide, making them a crucial area of focus. The rise of the tourism sector is often associated with the hospitality industry's impact on the environment. Through preliminary semi-structured interviews with eight respondents from diverse hotel experiences, the study analysed the current SFM initiatives in the context of the Malaysian hotel industry. The findings highlight that SFM practices follow a top-to-bottom sequential process, encompassing policy planning (strategic), awareness-raising (tactical), implementation (operational), and monitoring and improvement planning (operational). Emphasizing the significance of integrating SFM initiatives into day-to-day hotel operations, the study underscores the need for systematic and comprehensive sustainability practices. Moreover, this study makes a valuable contribution by developing Sustainable Facilities Management (SFM) initiatives that assess hotels' long-term commitment to sustainability, benefiting not only the industry but also the wider community. By focusing on SFM initiatives in the hospitality sector, this article offers crucial information to fuel the rapid growth of sustainable development within Malaysia's hospitality industry.